2012
DOI: 10.1051/0004-6361/201117556
|View full text |Cite
|
Sign up to set email alerts
|

The activity of main belt comets

Abstract: Context. Main belt comets represent a recently discovered class of objects. They are quite intriguing because, while having a Tisserand invariant value higher than 3, are showing cometary activity. Aims. We study the activity of the main belt comets making the assumption that they are icy-bodies and that the activity has been triggered by an impact. We try to determine the characteristics of this activity. We also try to determine if the nowadays impact rate in the main asteroid belt is compatible with the hyp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…From these results, they infer that in order for 133P to be active today, an impact must have occurred, by which material was removed from the surface to expose ice-rich layers. This idea is consistent with the study of Capria et al (2012) who found that impact rates in the MB are consistent with MBC activity being the result of impacts able to expose water ice at the surface of asteroids.…”
Section: Thermal Processing and Ice Survivalsupporting
confidence: 92%
“…From these results, they infer that in order for 133P to be active today, an impact must have occurred, by which material was removed from the surface to expose ice-rich layers. This idea is consistent with the study of Capria et al (2012) who found that impact rates in the MB are consistent with MBC activity being the result of impacts able to expose water ice at the surface of asteroids.…”
Section: Thermal Processing and Ice Survivalsupporting
confidence: 92%
“…The dust is left behind when ice sublimates and thus a dust mantle forms and grows very slowly with repeated perihelion passages, with not uniform thickness over the surface. Similar conclusions were reached by Capria et al (2010), who suggested that the activity of MBCs is due to a recent collision with a small body and that we are probably in the presence of a cratering event. The authors also estimated that a 5-km sized asteroid has an average lifetime of 2.2 Gyr, implying the observed MBCs are not primordial but rather fragments produced by collisional evolution.…”
Section: Activation Mechanismssupporting
confidence: 89%
“…Wherever MBCs originate from, their activity, although still not reliably understood, is likely triggered by the impact excavation of subsurface ice (Hsieh, Jewitt & Fernández 2004; Jewitt 2012) because completely exposed surface ice is unstable against sublimation at their heliocentric distances over Gyr time‐scales. According to Hsieh (2009) and Capria et al (2012), this hypothesis is in reasonable agreement with the present‐day impact frequency in the main belt.…”
Section: Introductionsupporting
confidence: 79%